Taiwan’s truth and reconciliation committee: the geopolitics of transitional justice in a contested state - Rowen, Ian (International journal of transitional justice, 2017)
This article examines Taiwan’s new president’s 2016 proposal for a truth and reconciliation commission (TRC), and addresses the ways in which this TRC serves domestic, regional and international policy goals. For Taiwan as a contested state, the TRC is part of a legitimation strategy that includes consolidation of a collective memory about earlier authoritarian state violence, cultural and political distinction from the irredentism and authoritarianism of China, and demonstration of adherence to international norms of democracy and human rights. We argue that the Taiwan case reveals the instrumentality of a TRC as a geopolitical strategy, particularly for relatively stable democracies facing external existential threats from an authoritarian country. We further demonstrate the need for ongoing research on transitional justice in Asia, and emphasize that political transitions are not only situated within nation states, but also in regions where TRCs may have profound geopolitical effects.